The science of psychology an appreciative view - King, Laura A.|q(Laura Ann) (Martin Stuart) (Boston McGraw-Hill Higher Education, 2008)
What is psychology? Psychology's scientific method; Biological foundations of behavior; Human development; Sensation and perception...
Includes bibliographical references (p. R1-R65) and index.
Keywords: Psychology -- Study and teaching; Tâm lý học